2019
DOI: 10.30682/nm1902b
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Dynamics of the European Economic Security in the Conditions of a Changing Socio-Economic Environment

Abstract: The speed the present world changes, is at least impressive. During the last decade the global socio-economic environment faced major adjustments dictated by globalisation, technological progress and political interests. The European Union seems to fail in keeping up with the changing environment. Thus, if in 2007 the European Union represented 30.7% of the global nominal GDP, then in 2016 it accounted only for 21.7% (World Bank). The economic positions of the European Union have declined much as compared to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 35 publications
0
11
0
2
Order By: Relevance
“…As noted by Kolot et al (2020), equally important for the economic security of the state is the development of the decent work institute in Ukraine, which is based on the socio-labor model "Work 4.0" and is the result of large-scale and multi-vector technical and technological innovations, organizational and business changes that create new opportunities, risks and threats for economically active people in the digital ecosystem. Ignatov (2019) places emphasis on the assessment of qualitative and quantitative indicators in the characteristics of EU member states, which makes it possible to determine the key triggers that cause violations of the country's economic security. Based on the correlation analysis of economic security indicators and integrated international ratings, it was established that corruption, bureaucracy, low entrepreneurship culture, terrorism, organized crime, gaps in development between regions, and migration have a destructive effect on the economic security of EU countries.…”
Section: Literature Reviewmentioning
confidence: 99%
“…As noted by Kolot et al (2020), equally important for the economic security of the state is the development of the decent work institute in Ukraine, which is based on the socio-labor model "Work 4.0" and is the result of large-scale and multi-vector technical and technological innovations, organizational and business changes that create new opportunities, risks and threats for economically active people in the digital ecosystem. Ignatov (2019) places emphasis on the assessment of qualitative and quantitative indicators in the characteristics of EU member states, which makes it possible to determine the key triggers that cause violations of the country's economic security. Based on the correlation analysis of economic security indicators and integrated international ratings, it was established that corruption, bureaucracy, low entrepreneurship culture, terrorism, organized crime, gaps in development between regions, and migration have a destructive effect on the economic security of EU countries.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Previous research resulted in a comprehensive understanding of national security through the prism of economic indicators such as public debt, GDP growth rate, capital investment, productivity, technology and institutions (Ignatov, 2019). Liapis et al (2013) point out that the recent economic and financial crisis has shown that highly indebted EU countries are economically vulnerable as a result of their financial and credit position.…”
Section: Literature Reviewmentioning
confidence: 99%
“…As mentioned above, the research on economic security mainly focuses on nations and supranational regions, identifying and evaluating key internal and external risk factors and facilitators [ 22 , 23 , 24 ], with a theoretical basis in political economy and the school of marginalism [ 25 ]. Recently, academic interest has been extended to the issue of RES within a country, especially in Russia and Ukraine.…”
Section: Literature Review and Analytical Framework Of Resmentioning
confidence: 99%